Relationship Between Body Mass Index and Fat Mass Percentage with Proprioception in Children - Herrera-Valenzuela, T (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background/Objectives: Childhood obesity is linked to motor and sensorimotor impairments, including proprioceptive deficits. While research has predominantly focused on lower limb proprioception, less is known about the impact on upper limbs. This study investigated the relationship between body mass index, body fat percentage, and proprioception of children aged 11–12 years. Methods: A quantitative, correlational, observational design was employed. BMI was calculated from weight and height measurements, body fat percentage was assessed via bioelectrical impedance analysis, and proprioception was measured using an active repositioning test with inertial sensors in 44 children. Results: Significant correlations were found between BMI and positional errors in the shoulder (r = 0.64, p < 0.001), elbow (r = 0.36, p = 0.007), and knee (r = 0.42, p = 0.002). Regarding body fat percentage, significant correlations were observed with positional errors in the shoulder (r = 0.28, p = 0.031), elbow (r = 0.46, p < 0.001), and knee (r = 0.29, p = 0.030). Regression analysis showed that BMI and body fat percentage significantly predicted positional errors in the shoulder, elbow, and knee. In the shoulder joint, girls demonstrated lower positional errors compared to boys, influenced by both BMI (β = −1.36, p = 0.015) and body fat percentage (β = −3.00, p < 0.001). Conclusions: Higher BMI and body fat percentage are associated with shoulder, elbow, and knee joint proprioceptive deficits. Interventions targeting weight reduction and proprioceptive training may mitigate these deficits and promote sensorimotor function in children. © 2025 by the authors.